Physiotherapeutic Approach In The Treatment Of Lung Injuries Caused By Electronic Cigarettes: An Integrative Review - De Vasconcelos, Jessica Leandra Almeida; Belem, Antônio Rhamon Da Silva; Da Costa, Priscila Andrade; Costa, Marcilene de Jesus Caldas; Soares, Carla Nogueira; Araújo, Priscila Xavier; Moreira, Rodrigo Canto; Moura, Sting Ray Gouveia; Tannus, Lorena de Oliveira; Fonseca, Raiane Correia (Seven Editora, 2023)
Electronic cigarettes emerged as an alternative to replace conventional cigarettes, however, their consumption has grown among youth and non-smoking adults, and little is known about their real harms to the body as a whole, but especially to the respiratory system. The objective of this research was to highlight the contributions of respiratory physiotherapy in the treatment of Lung Injury Associated with Electronic Cigarette Use (EVALI). This study is characterized as an integrative review of literature of a basic nature of the descriptive and qualitative type. Thus, it aimed to show how the physiotherapist can intervene in EVALI. In this context, it is understood that their interventions are related to the clinical manifestations present in individuals, because their recurrent consumption causes damage to the lung, allowing the generation of pathophysiological processes caused by inflammation and aggression of the epithelium. DOI: https://doi.org/10.56238/colleinternhealthscienv1-116